2014
DOI: 10.1016/j.ahj.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and resting pulse rate in older adults: Findings from a randomized controlled trial

Abstract: Background Elevated resting pulse rate (RPR) is a well-recognized risk factor for adverse outcomes. Epidemiological evidence supports the beneficial effects of regular exercise for lowering RPR, but studies are mainly confined to persons younger than 65 years. We set out to evaluate the utility of a physical activity (PA) intervention for slowing RPR among older adults. Methods A total of 424 seniors (ages 70-89 years) were randomized to a moderate intensity PA intervention or an education-based “successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These results suggest that increased PA may be sufficient to affect the autonomic tone of adults, similar to exercise modalities that have been shown to do so (Karavirta et al, 2009, Ueno andMoritani, 2003). However, in contrast to our results, others have reported that in older adults, no statistically significant correlation was identified between resting HR and leisure-time PA (O'Hartaigh et al, 2014, Miranda et al, 2014 .…”
Section: Physical Activity and Heart Ratesupporting
confidence: 47%
“…These results suggest that increased PA may be sufficient to affect the autonomic tone of adults, similar to exercise modalities that have been shown to do so (Karavirta et al, 2009, Ueno andMoritani, 2003). However, in contrast to our results, others have reported that in older adults, no statistically significant correlation was identified between resting HR and leisure-time PA (O'Hartaigh et al, 2014, Miranda et al, 2014 .…”
Section: Physical Activity and Heart Ratesupporting
confidence: 47%
“…Aerobic exercise has multiple positive effects on health outcomes in healthy elderly individuals including increased cardiovascular performance 1 , 22 . Contrary to this, Hartaigh et al found that twelve months of moderate intensity aerobic training did not improve RPR among older adults 23 . Hence, more prospective trials are needed to prove the same.…”
Section: Discussionmentioning
confidence: 87%
“…Physical activity (PA) promotes a broad spectrum of health benefits, in particular, by reducing the risk attributable to CV disease and its sequelae, but prior studies have largely focused on populations younger than 65. To address this gap in knowledge, the efficacy of a moderate‐intensity PA intervention for lowering resting pulse rate (RPR) in older adults was recently evaluated . RPR serves as an important predictor of adverse cardiovascular risk and is an indicator of physical fitness .…”
mentioning
confidence: 99%
“…To address this gap in knowledge, the efficacy of a moderate-intensity PA intervention for lowering resting pulse rate (RPR) in older adults was recently evaluated. 7 RPR serves as an important predictor of adverse cardiovascular risk 8 and is an indicator of physical fitness. 9 Data from the Lifestyle Interventions and Independence for Elders (LIFE) Pilot Study, 7 which included 424 individuals aged 70 to 89 years, showed that a 12-month moderate-intensity aerobic training program failed to lower RPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation